High ICP as trigger of proinflammatory IL-6 cytokine activation in aneurysmal subarachnoid hemorrhage - Graetz, Daniela; Nagel, Alexandra; Schlenk, Florian; Sakowitz, Oliver; Vajkoczy, Peter; Sarrafzadeh-Khorassani, Asita (Neurological research, 2010)
OBJECTIVE: There is a rising debate about the role of inflammation in the pathogenesis of complications after aneurysmal subarachnoid hemorrhage (SAH) such as intracranial hypertension (intracranial pressure, ICP >20 mmHg). This study aimed to analyse the origin of interleukin-6 (IL-6) in respect to ICP and cerebral metabolism in SAH patients. - METHODS: Prospectively, IL-6 was measured in three compartments, the extracellular fluid (ECF) monitored by cerebral microdialysis (MD), cerebrospinal fluid (CSF) and plasma for 10 days after SAH (days 0-4, three times daily; days 5-10, two times daily). Patients were classified having intracranial hypertension (n=7) or normal ICP (n=17) during 10 days after bleeding. Glasgow outcome scale (GOS) was assessed after 3 and 6 months. - RESULTS: Patient groups were comparable for age, WFNS and Fisher grade. Intracranial hypertension was associated with an inflammatory response, indicating activation of the inflammatory cascade in the brain (ECF) and systemic circulation with high IL-6 and C-reactive protein (CRP) plasma levels after SAH, the latter associated with unfavourable outcome. The data suggest the ECF but not the CSF as main origin of IL-6 in the systemic circulation in the presence of intracranial hypertension in SAH. - DISCUSSION: Intracranial hypertension is associated with a strong activation of the inflammatory cascade in the brain and systemic circulation, and might be underestimated as proinflammmatory trigger in the pathogenesis of complications after SAH. Future therapies targeting anti-inflammatory response in plasma may help to reduce the inflammatory cascade responsible for development of intracranial hypertension.